Vision and visuality: Regimes of knowledge and appropriation of others in ethnographic museums and ethnographic film - Simić Marina (Glasnik Etnografskog Instituta SANU, 2010)
This paper presents some similarities between epistemological paradigms in anthropological museum exhibitions and ethnographic films. Both the museum and ethnographic films are analysed as the models of representations based on the domination of vision as mode of knowledge through which curators and film makers produce subjects of their representations. Paradigmatic shifts in the 1980s with the critique of 'modern constitution' and domination of vision as a major 'sense of knowledge' in Western thought had great impact on museum curators and ethnographic film authors who in the last two decades tried to incorporate those changes in their practices. The paper presents some examples of film and ethnographic practices that followed those theoretical shifts and try to deconstruct their own representational practices and evaluate the results of those attempts.